A generalised modelling discussion for portable wireless base stations during emergencies. (2018) - LeBlanc, Larry J.
The occurrence of natural disasters and emergencies creates the need for communication between and among emergency responders, the region's population, and other governmental and non-governmental agencies and organisations. Key information that is to be disseminated among these groups must rely on communication networks that may have been rendered partially or fully inoperable. In these scenarios, temporary wireless telecommunications infrastructure can be utilised to provide the links necessary for critical communications. While the deployment of temporary mobile networks and other wireless equipment during the aftermath of disasters has been successfully accomplished by governmental agencies and network providers following previous disasters, there appears to be little optimisation effort involved with respect to maximising key performance measures of the deployment or minimising overall cost to deploy. This work does not focus on the question of what entity will operate the portable base stations or wireless equipment utilised during a disaster, only the question of optimising placement for planning and real time management. I examine the modelling and optimisation of the deployment of a wireless infrastructure prior to, during, and after an emergency or crisis.